Public Information Disclosure in State Islamic Institutes: Learning from Universitas Islam Negeri - Munadi, Muhammad; Sulistiyono, Tato Priyo; Alwiyah, Noor; Juhaidi, Ahmad (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
This study determined the public information disclosure implementation model at the State Islamic University of Walisongo in Semarang. This study used content analysis research, with the data originating from the website, the documents downloaded from the website related to public information disclosure activities at UIN Walisongo Semarang, and the developments uploaded on the website. The data analysis used content analysis through unitizing, sampling, recording-reducing, and inferring or drawing conclusions. The study results showed that the public information disclosure implemented by UIN Walisongo Semarang through the Information and Documentation Management Officer (PPID) institution had its services offline and online. A representative place was provided offline, and the PPID website was separated from the leading website online. The PPID website contained complete information regarding profiles and types of report information by existing regulations. The types of data and reports had institutional dimensions and institutional implementation. Furthermore, it was possible for mutually reinforcing linkages to occur, whereas a good and clean institution reflected an excellent and clean executor or vice versa.